Effects of Wheat Germ and Its Combination With Antibiotics on Metabolic and Gut Health Outcomes in Western Diet-Fed Mice. (7th June 2021) - Tilla, Tizazu; Alake, Sanmi; Kaur, Amritpal; Dotimas, Levin; Hermann, Evan; Gashu, Dawd; Smith, Brenda; Lucas, Edralin
Abstract: Objectives: This study evaluated whether wheat germ (WG) alone or in combination with antibiotics (Ab) will ameliorate metabolic and gut integrity and inflammatory markers in mice fed a Western diet (WD). Methods: Six-wk-old male C57BL/6 mice were randomly assigned ( n  = 7–8/group) to three dietary treatement groups: WD (60% fat kcal), WD + WG (10% wt/wt) and WD + WG + Ab (1 mg/mL ampicillin, metronidazole, neomycin, and ampothericin B plus 0.5 mg/mL vancomycin cocktail added in drinking water) for 4 wks. Food intake and body weights were assessed daily throughout the study. Tissues were collected and assessments included clinical chemistry parameters, intaperitoneal glucose tolerance test (IPGTT), body composition by dual-energy x-ray absorptiometry, and gut integrity and inflammatory markers by qPCR. Effects of treatment were analyzed with one-way ANOVA using SPSS software and P < 0.05 was considered significant. Results: Food intake differed significantly ( P  < 0.0001) between groups, with the WD + WG having the highest and WD + WG + Ab having the lowest intake. Final body weight ( P  < 0.0001) and fat mass ( P  < 0.0001) was lowest in the WD + WG + Ab and similar for WD and WD + WG groups. There was no difference in lean mass among the groups. IPGTT area under the curve ( P  < 0.0001) and serum total cholesterol ( P  = 0.023) were significantly reduced and fasting glucose tended ( P  = 0.091) to be lower in the WD + WG + Ab group. Mice in the WD + WG + Ab group also had higher cecal tissue and cecal content weights ( P  < 0.0001) as well as the ileal gene expression of the tight junction protein occludin ( P  = 0.008) compared to the other groups. On the other hand, WD + WG fed mice had significantly higher ileal gene expression of the anti-inflammatory cytokine, interleukin (IL)-10, compared to WD ( P  = 0.05) and WD + WG + Ab ( P  = 0.035). Conclusions: Although WG alone promoted a gut anti-inflammatory response, it was not as effective as the combination of WG and antibiotics at improving metabolic outcomes. These positive effects of WD + WG + Ab on metabolic outcomes were likely due to a reduction in food intake resulting in lower body weight and body fat. Future studies should investigate the contribution of antibiotics, the role of the gut microbiota, and the impact of long-term antibiotic use. Funding Sources: Oklahoma Agriculture Experiment Station and the Jim and Lynn Williams Professorship.